Dental and skeletal effects of palatal expansion techniques: a systematic review of the current evidence from systematic reviews and meta‐analyses. (23rd March 2016) - Bucci, R.; D'Antò, V.; Rongo, R.; Valletta, R.; Martina, R.; Michelotti, A.
Summary: The aim was to assess the quality and to summarise the findings of the Systematic Reviews (SRs) and Meta‐Analyses (MAs) on the dental and skeletal effects of maxillary expansion. Electronic and manual searches have been independently conducted by two investigators, up to February 2015. SRs and MAs on the dentoalveolar and skeletal effects of fixed expanders were included. The methodological quality was assessed using the AMSTAR (A Measurement Tool to Assess Systematic Reviews). The design of the primary studies included in each SR/MA was assessed with the LRD (Level of Research Design scoring). The evidence for each outcome was rated applying a pre‐determined scale. Twelve SRs/MAs were included. The AMSTAR scores ranged from 4 to 10. Two SRs/MAs included only RCTs. The current findings from SRs/MAs support with high evidence a significant increase in the short‐term of maxillary dentoalveolar transversal dimensions after Rapid Maxillary Expansion (RME). The same effect is reported with moderate evidence after Slow Maxillary Expansion (SME). However, there is moderate evidence of a non‐significant difference between the two expansion modalities concerning the short‐term dentoalveolar effects. With both RME and SME, significant increase of skeletal transversal dimension in the short‐term is reported, and the skeletal expansion is always smaller than the dentoalveolar. Even though dental relapse to some extent is present, long‐term results of the dentoalveolar effects show an increase of the transversal dimension, supported by moderate evidence for RME and low evidence for SME. Skeletal long‐term effects are reported only with RME, supported by very low evidence.